Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0189119
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to evaluate the influence of environmental conditions on eDNA detection success in aquatic ecosystems

Abstract: The use of environmental DNA (eDNA) to determine the presence and distribution of aquatic organisms has become an important tool to monitor and investigate freshwater communities. The successful application of this method in the field, however, is dependent on the effectiveness of positive DNA verification, which is influenced by site-specific environmental parameters. Factors affecting eDNA concentrations in aquatic ecosystems include flow conditions, and the presence of substances that possess DNA-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 58 publications
1
100
0
Order By: Relevance
“…However, we discovered that several aspects of eDNA metabarcoding require further optimization prior to implementation in established monitoring programs. The impact of vertical zonation on eDNA patterns (Minamoto et al, ), temporal stability (Bista et al, ), abiotic influences on eDNA persistence (Stoeckle et al, ), and the correlation between eDNA signal strength and true abundance (Jo et al, ), have received little attention to date and require more investigation. In agreement with the growing body of eDNA studies in the literature, the data from the Aramoana site indicate that eDNA metabarcoding surveys, when appropriately executed, will be a powerful tool in the management and conservation of marine environments.…”
Section: Resultsmentioning
confidence: 99%
“…However, we discovered that several aspects of eDNA metabarcoding require further optimization prior to implementation in established monitoring programs. The impact of vertical zonation on eDNA patterns (Minamoto et al, ), temporal stability (Bista et al, ), abiotic influences on eDNA persistence (Stoeckle et al, ), and the correlation between eDNA signal strength and true abundance (Jo et al, ), have received little attention to date and require more investigation. In agreement with the growing body of eDNA studies in the literature, the data from the Aramoana site indicate that eDNA metabarcoding surveys, when appropriately executed, will be a powerful tool in the management and conservation of marine environments.…”
Section: Resultsmentioning
confidence: 99%
“…We found that crucian carp density (CPUE) positively influenced eDNA detection probability and DNA copy number. Density is frequently reported to improve detection probability of aquatic species due to more eDNA deposition in the environment (Buxton, Groombridge, Zakaria, & Griffiths, ; Schmelzle & Kinziger, ; Stoeckle et al., ), but this relationship is highly variable across study systems and species due to influence of external factors (Buxton, Groombridge, & Griffiths, ; Goldberg et al., ; Strickler et al., ). For example, increase in water temperature coincided with breeding activity and heightened DNA release in other fish and amphibian species (Buxton, Groombridge, Zakaria, & Griffiths, ; Bylemans et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Links established between eDNA and pH support greater detectability, concentration, and persistence of eDNA in more alkaline waters (Barnes et al., ; Goldberg et al., ; Strickler et al., ). Conductivity relates to total dissolved solids (TDS) and sediment type, which can impair eDNA detection due to release of inhibitory substances and their capacity to bind DNA (Buxton, Groombridge, & Griffiths, ; Stoeckle et al., ). Vegetated ponds reduce UV exposure thereby preserving eDNA (Barnes et al., ), and are susceptible to terrestrialisation which can create anoxic conditions that may slow eDNA degradation (Barnes et al., ; Pilliod et al., ; Weltz et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the various physiochemical factors of lotic freshwater environments such as turbidity and conductivity are suggested to influence eDNA detection (Buxton, Groombridge, & Griffiths, 2017). However, studies rarely consider the importance of these factors in their sampling and analysis of eDNA data (Stoeckle et al, 2017). Comparative modelling approaches that also account for eDNA detection rates allow decision-makers to weigh the costs and benefits of sampling methods to better understand population declines, fill data gaps, and improve monitoring programs (Jackson et al, 2016;Nichols et al, 2008).…”
Section: Introductionmentioning
confidence: 99%